Analisis Kreativitas Guru dalam Penggunaan Media Pembelajaran Kelas IV SDN Kebon Cau I Kabupaten Tangerang - Anggraeni, Serly; Sunaryo, Sunaryo; Suhendar, Asep (Lembaga Yasin AlSys, 2023)
The focus of research on this research problem is to find out creativity in using learning media in Indonesian language subjects for class IV SDN Kebon Cau I Tangerang Regency. This study aims to increase the creativity of teachers in the learning process through the use of learning media in Indonesian language subjects. This study uses a qualitative descriptive research method. In collecting data researchers used the method of observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the research that focused on teacher creativity at SDN Kebon Cau I Tangerang Regency were quite creative but not yet optimal, the teacher's methods paid little attention to strategies in teaching. In the use of learning media. Whereas teachers use media there are obstacles in making their own media an obstacle with finances and also time. So that the media that is often used by homeroom teachers of class IV B more often utilizes blackboard media, internet media, and teacher thematic books, as well as student thematic books, so that students become bored or bored during the learning process, this has an impact on decreasing student scores